The human right to science: From fragmentation to comprehensive implementation? - Peter Bille Larsen; Marjorie Pamintuan (South Centre, 2022)
In times when the role of science in society is more debated than ever in polarized, politicized and partial terms, what is the role for the human right to science and rights-based approaches? The right to science remains poorly understood and neglected in both national and global human rights processes. Beyond defending the freedom of scientific expression, upholding the right to science is arguably fundamental to resolving key sustainability challenges of our times from climate change and the biodiversity crisis to global health and pandemics. The global COVID-19 pandemic has revealed persistent global inequalities not least in terms of how the privatization of science and current intellectual property regimes hinder just and equitable responses to access science and its benefits. This prompts the need for a shift from single-issue approaches to comprehensive and systematic treatment of the right to science as a bundle of human rights across multiple arenas to counter fragmentation and silo-tendencies.
Keywords: 300; 2030 Agenda for Sustainable Development; Access to Medicines; Access to Science; Biodiversity; Climate Change; COVID-19; Global Health; Human Rights; Inequalities; Innovation; Intellectual Property; Pandemic; Right to Science; Science; Sustainability; Sustainable Development Goals (SDGs); Swiss Commission for UNESCO; Technology; UNESCO